Barriers to BRCA, HRD, and HRRm testing despite increased utilization: U.S. physician survey results. Issue 28 (1st October 2022) - Szamreta, Elizabeth A.; Ning, Ning; Jackson, Bianca; Shah, Ruchit; Aggarwal, Jyoti; Adeboyeje, Gboyega; Hussain, Arif
Abstract : 380 Background: Despite increasing use of breast cancer (BRCA) gene and homologous recombination deficiency/ homologous recombination repair gene mutation(s) (HRD/HRRm) testing, barriers to uniform adoption of these tests to inform patient management remain. The purpose of this study was to identify potential barriers to BRCA, HRD, and HRRm testing from the physician's perspective. Methods: A cross-sectional online survey was sent to a US representative sample of primary care providers, medical oncologists, urologists, and surgeons, including both users and non-users of the tests. Physician demographics, practice characteristics, barriers (reimbursement, knowledge, logistical), and strategies to alleviate barriers were collected. Descriptive analysis was conducted via SASv9.4. Results: Three hundred physicians participated in this survey (49.7 years of age and 17.9 years in clinical practice on average). Most respondents (94.3%) reported at least 1 barrier to test use (BRCA 94.0%, HRD 91.3%, HRRm 90.3%). The most common barrier was the challenge in obtaining prior authorizations (BRCA 74.0%, HRD 80.0%, HRRm 83.5%). Other commonly reported barriers included test not being covered by insurance (BRCA 64.8%, HRD 61.8%, HRRm 67.6%), insurance policies restricting certain genomic tests to a particular lab/test provider (BRCA 64.0%, HRD 66.5%, HRRm 67.4%), and unclear/inconsistent payer policies for test coverage (BRCA 63.6%, HRD 63.6%, HRRm 66.7%). Physicians were more likely to report barriers to HRD/HRRm testing compared to BRCA testing. More reimbursement-related barriers were reported by primary care providers vs. other physicians. Physician/patient education, collaboration with specialists, standardization in test guidelines, and improvement in test interpretation were reported as key strategies to improving further test adoption in patient management. Conclusions: The results highlight that physicians have concerns about reimbursement-related, knowledge-related, and logistical barriers that may impact clinical optimization. Addressing these barriers to improve oncology care is of utmost importance.Barriers to test adoption reported by physicians (N = 300), %. Barrier BRCA HRD HRRm Reimbursement Obtaining prior authorizations 74.0 80.0 83.5 Test not covered by patient insurance 64.8 61.8 67.6 Insurance policies restricting certain genomic tests to a particular lab/test provider 64.0 66.5 67.4 Unclear/inconsistent payer coverage policies 63.6 63.6 66.7 Knowledge Lack of readily available genetic counselors for test interpretation 64.4 65.2 68.2 Unaware of corresponding therapy or clinical trials that may benefit patients 57.1 68.1 69.0 Lack of multidisciplinary knowledge-sharing within institution 49.3 58.2 54.7 Logistical Test turnaround time 50.0 62.1 65.1 Lack of contracts with external testing laboratories to perform genomic testing 49.2 55.2 57.1